Carbon Sink-to-Source Transition Is Coordinated with Establishment of Cell-Specific Gene Expression in a C4 Plant. - Wang, JL (1993)
Plants that use the highly efficient C4 photosynthetic pathway possess two types of specialized leaf cells, the mesophyll and bundle sheath. In mature C4 leaves, the CO2 fixation enzyme ribulose-1,5-bisphosphate carboxylase (RuBPCase) is specifically compartmentalized to the bundle sheath cells. However, in very young leaves of amaranth, a dicotyledonous C4 plant, genes encoding the large subunit and small subunit of RuBPCase are initially expressed in both photosynthetic cell types. We show here that the RuBPCase mRNAs and proteins become specifically localized to leaf bundle sheath cells during the developmental transition of the leaf from carbon sink to carbon source. Bundle sheath cell-specific expression of RuBPCase genes and the sink-to-source transition began initially at the leaf apex and progressed rapidly and coordinately toward the leaf base. These findings demonstrated that two developmental transitions, the change in photoassimilate transport status and the establishment of bundle sheath cell-specific RuBPCase gene expression, are tightly coordinated during C4 leaf development. This correlation suggests that processes associated with the accumulation and transport of photosynthetic compounds may influence patterns of photosynthetic gene expression in C4 plants.